Case of Extensive Polydactyly of Foot - Sharma, R N (Indian Journal of Plastic Surgery, 1995)
A case of extensive polydactyly of the foot is being reported because of its rarity. The result of surgery has been satisfactory from cosmetic and functional points of view. A comparison with similar cases reported in the literature is included.